2022
DOI: 10.1177/20539517211072190
|View full text |Cite
|
Sign up to set email alerts
|

Public views of the smart city: Towards the construction of a social problem

Abstract: Digitization and datafication of public space have a significant impact on how cities are developed, governed, perceived and used. As technological developments are based upon political decisions, which impact people’s everyday lives, and from which not everyone benefits or suffers equally, we argue that ‘the smart city’ should be part of continuous public debate; that it should be considered and treated as a social problem. Through nine focus groups, we invited respondents to explore and discuss instances and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…3–10) found that smart city technologies are important in local economic development where they are of low priority for local governments. Rijshouwer et al (2022, pp. 1–11) found that citizens in Rotterdam do not experience the smart city as a social and actionable problem in their survey of 91 people.…”
Section: Discussionmentioning
confidence: 99%
“…3–10) found that smart city technologies are important in local economic development where they are of low priority for local governments. Rijshouwer et al (2022, pp. 1–11) found that citizens in Rotterdam do not experience the smart city as a social and actionable problem in their survey of 91 people.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include visual and verbal vignettes based on different kinds of surveillance technologies (Mariën and Poels 2020) or scenarios of smart city futures (Butot et al 2020;Jameson, Richter, and Taylor 2019), gamified surveys challenging players to identify surveillant objects in a virtual smart city (Rijshouwer, Leclercq, and van Zoonen 2022), and escape rooms with surveillance storylines (Kihara, Lomas, and Bendor 2019). Although these studies have slightly different epistemological approaches to the phenomenon of "subjective experience," all highlight feelings of exposure to smart city surveillance, which is experienced as opaque in its functioning (Butot et al 2020;Jameson, Richter, and Taylor 2019;Rijshouwer, Leclercq, and van Zoonen 2022;Mariën and Poels 2020). To make sense of their uncertainties about surveillance, people differentiate between "personal" and "impersonal" data, public and private actors, and the purposes behind data collection ( Van Zoonen 2016;Mariën and Poels 2020).…”
Section: Studying Subjective Experiences Of Smart City Surveillancementioning
confidence: 99%
“…However, results across the studies also suggest that such cognitive assessments of smart city technologies are not made in everyday life, and that most people seem to reluctantly accept surveillance because it is too pervasive to consciously reflect on all the time. With an eye on future developments, people see invasive smart city surveillance scenarios as inevitabilities regardless of their values, preferences, and priorities (Butot et al 2020;Rijshouwer, Leclercq, and van Zoonen 2022). These results can be compared against research highlighting a "privacy paradox," where people's statements about valuing privacy are incongruous with their disclosure of personal information (Acquisti and Grossklags 2003).…”
Section: Studying Subjective Experiences Of Smart City Surveillancementioning
confidence: 99%
“…The digitalization of the public space has recently had a significant impact on how cities are being perceived and governed (Rijshouwer et al, 2022). Indeed, over the last years, smart city innovations, and corresponding digitally enhanced and data-driven governance practices, have been suggested to address urban problems (Luque-Ayala and Marvin, 2015).…”
Section: Interpreting Digital Governance and The Smart City Through T...mentioning
confidence: 99%